The Effect and Mechanism of Transcranial Direct Current Stimulation on Episodic Memory in Patients With Mild Cognitive Impairment - Gu, Jun; Li, Da; Li, Zhaohui; Guo, Yuan; Qian, Fuqiang; Wang, Ying; Tang, Li (Frontiers in Neuroscience, 2022)
Objective: This study aimed to investigate the efficacy of transcranial direct current stimulation (tDCS) on episodic memory in patients with mild cognitive impairment (MCI) and analyze the neural mechanism of TDCS therapy from the perspective of neuroelectrophysiologic parameters. Methods: Forty MCI patients were recruited and randomly divided into sham group (n=20) and tDCS group (n=20). Patients in the tDCS group were treated with tDCS instrument for 20 min, once a day, for 5 days. Patients in the sham group were treated with sham stimulus. Montreal Cognitive Assessment Scale (MoCA), Wechsler Memory Scale (WMS), and event-related potential (ERP) (amplitude and latency of P300 wave) were comparatively assessed between the two groups at pre-treatment, 5 days and 4 weeks post-treatment points. Results: The two groups showed no significant difference in any of the assessed parameters at pre-treatment (P > 0.05). At 5-day post-treatment, memory quotient (MQ) score in the tDCS group significantly increased (P < 0.05), scores of picture memory, visual regeneration, logical memory, memory span, visual regeneration-delay and logical memory-delay were significantly increased compared to pre-treatment (P < 0.01). The P300 amplitude significantly increased, and its latency significantly shortened (P < 0.01). Four weeks post-treatment, the scores of MQ and visual regeneration-delay in tDCS group increased, compared to pre-treatment (P < 0.05); picture memory, visual regeneration, logical memory, memory span and logical memory-delay improved (P < 0.01); the P300 amplitude increased and its latency shortened (P < 0.01). At 5-day and 4-week post-treatment points, tDCS group, compared with the sham group (P＜0.01) exhibited greater scores of MQ, picture memory, visual regeneration, logical memory, memory span, visual regeneration-delay, and logical memory-delay, increased P300 amplitude, and shortened P300 latency. Similarly, the tDCS group showed higher MQ score at 5-day post-treatment (P < 0.05) and 4-week post-treatment (P < 0.01). Before treatment and after 5 days of treatment, P300 amplitude and latency difference were positively correlated with MQ difference (P < 0.05). Conclusion: TDCS improved episodic memory in MCI patients, and the effect lasted for 4 weeks. Changes in ERP (P300) suggested that tDCS could promote changes in brain function.